Investigation of Antioxidant Status in Iraqi Patients with Beta- Thalassemia Major - Jamela Jouda (Journal of Global Pharma Technology, 2017)
Background: Oxidative stress is the most common complication in Beta-thalassemia patients due to ironover load that is resulted from long life blood transfusion leading to growth retardation, delay of sexualmaturation, and later involvement of the liver, heart, and endocrine system. Aim of study: Assess of someantioxidant parameter status in serum and saliva of patients with beta-thalassemia major in comparisonwith control subjects. Methodology: Total antioxidant (TAO), glutathione (GSH), uric acid (UA), urea (U)and albumin were investigated in serum and saliva samples of all subjects. Results: Albumin level inserum is significantly (P ˂ 0.00001) decreased in patients group (3.27 ± 0.17 g/dl) from that in controlgroup (3.59 ± 0.13 g/dl). However, TAO level was significantly elevated (P = 0.031) from (3.14 ± 1.38U/ml) in the saliva of control group up to (4.09 ± 1.76 U/ml) in the saliva of patients group as well assignificant difference (P = 0.02) in salivary fraction index (Sf) only for TAO which is elevated from 0.47 incontrol group up to 0.56 in patients group. Conclusion: The findings of this study indicated that theserum level of albumin can be used as a good marker to reflect the liver status in TM patient in additionto other conventional markers. Also this study suggested that saliva can be act as an alternative sampleto assess the antioxidant status in TM patients but need further investigation.Keywords: Beta thalassemia major, Iron overload, Antioxidant, Saliva.